2011
DOI: 10.1371/annotation/fe4fca93-8211-430e-bfe0-8a371b9cc20d
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Expression and Function of Androgen Receptor Coactivator p44/Mep50/WDR77 in Ovarian Cancer

Abstract: Hormones, including estrogen and progesterone, and their receptors play an important role in the development and progression of ovarian carcinoma. Androgen, its receptor and coactivators have also been implicated in these processes. p44/Mep50/WDR77 was identified as a subunit of the methylosome complex and lately characterized as a steroid receptor coactivator that enhances androgen receptor as well as estrogen receptor-mediated transcriptional activity in a liganddependent manner. We previously described dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Second, DHT (e.g., 10–100 nM) considerably induced cell proliferation of established AR-positive lines [26,47,71,72,73,74], and anti-androgens, including flutamide/hydroxyflutamide and bicalutamide, blocked the stimulatory effects of DHT [47,72,73,75]. Other androgens, such as testosterone [47], androstenedione [74], and a synthetic androgen methyltrienolone [76], were also shown to increase the proliferation of cancer cells. Third, DHT increased S-phase population in a primary culture [55] or OVCAR3 [73].…”
Section: Role Of Androgens and Ar Signaling In Ovarian Cancer Progmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, DHT (e.g., 10–100 nM) considerably induced cell proliferation of established AR-positive lines [26,47,71,72,73,74], and anti-androgens, including flutamide/hydroxyflutamide and bicalutamide, blocked the stimulatory effects of DHT [47,72,73,75]. Other androgens, such as testosterone [47], androstenedione [74], and a synthetic androgen methyltrienolone [76], were also shown to increase the proliferation of cancer cells. Third, DHT increased S-phase population in a primary culture [55] or OVCAR3 [73].…”
Section: Role Of Androgens and Ar Signaling In Ovarian Cancer Progmentioning
confidence: 99%
“…It was additionally shown that DHT induced cell motility and invasion of an ovarian cancer line [79]. Methyltrienolone [76] and another AR ligand, medroxyprogesterone [80], also increased the ability of cell invasion of AR-positive ovarian cancer lines, although the latter is classified as a progestin. All of these studies have thus demonstrated in vitro and in vivo data indicating that androgens promote cell proliferation/invasion of ovarian cancer via the AR pathway.…”
Section: Role Of Androgens and Ar Signaling In Ovarian Cancer Progmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies further indicate that the interaction of the AR-ligand and co-activator plays an important role in gene expression. The AR co-activator, p44/Mep50, a subunit of the methylosome complex, enhances AR-mediated transcription activity in a ligand-dependent manner [22,23]. While it may act as a nuclear co-activator in breast cancer cells, p44 is also present in substantial quantities in the cytoplasm of terminal ductal lobular units [22,23].…”
Section: Androgen and Other Non-peptide Hormones Act Via Different Rementioning
confidence: 99%
“…The AR co-activator, p44/Mep50, a subunit of the methylosome complex, enhances AR-mediated transcription activity in a ligand-dependent manner [22,23]. While it may act as a nuclear co-activator in breast cancer cells, p44 is also present in substantial quantities in the cytoplasm of terminal ductal lobular units [22,23]. When overexpressed by MCF7 breast cancer cells, p44 has been shown to enhance proliferation and invasiveness [22].…”
Section: Androgen and Other Non-peptide Hormones Act Via Different Rementioning
confidence: 99%